2020
DOI: 10.3389/fvets.2019.00505
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter hepaticus, the Cause of Spotty Liver Disease in Chickens: Transmission and Routes of Infection

Abstract: The epidemiology of Spotty Liver Disease (SLD) was investigated by assaying 1,840 samples collected from layer chickens and the environment in poultry farms across Australia for the presence of Campylobacter hepaticus, the agent responsible SLD in chickens. A C. hepaticus specific PCR and bacterial culture were used. Results showed that birds could be infected with C. hepaticus up to 8 weeks before clinical SLD was manifested. In addition, birds could be infected long before laying starts, as young as 12 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 30 publications
3
41
0
Order By: Relevance
“…The disease started as an increased mortality rate with no premonitory signs. Recently, it has been reported that birds can be infected with C. hepaticus without any clinical signs regardless of the onset of laying, without any clinical SLD (Phung et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The disease started as an increased mortality rate with no premonitory signs. Recently, it has been reported that birds can be infected with C. hepaticus without any clinical signs regardless of the onset of laying, without any clinical SLD (Phung et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The flock consisted of 18 000 birds with 90% production. The disease started as an acute disease with increased Spotty liver disease (SLD) is an acute bacterial disease that is caused by Campylobacter hepaticus (Phung et al 2020). SLD causes significant morbidity as well as mortality in poultry flocks throughout the world (Van et al 2017b).…”
Section: Clinical Findings and Sample Collectionmentioning
confidence: 99%
“…Testing may also be used for SLD surveillance which could contribute to disease prevention and control. While culture of C. hepaticus from samples collected in the field is difficult [9] PCR testing has proved to be more sensitive and is able to detect C. hepaticus in bile samples, intestine content samples and faeces [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The methods available to date to detect C. hepaticus from SLD cases have been limited to culture and DNAbased approaches . Culturing the bacterium from microbiologically complex samples, such as faeces or environmental samples, is a tedious and time-consuming task as it takes 3-7 days to grow on culture plates and culture can be challenging as a selective medium for C. hepaticus isolation is yet to be developed (Phung et al, 2020). When grown on nutrient agar or Brucella agar supplemented with blood, other campylobacters routinely present in samples, like Campylobacter coli, Campylobacter jejuni and many other bacteria, out-grow the plate and make it difficult to identify C. hepaticus.…”
Section: Introductionmentioning
confidence: 99%
“…A qPCR assay and an end-point PCR assay using primers targeting the glycerol kinase gene, one of the unique genes present in C. hepaticus, have been successfully used to detect C. hepaticus from liver, gut, bile, faeces and environmental samples Phung et al, 2020). A multiplex PCR assay employing primers for the C. jejuni-specific hippuricase (hipO) gene and the C. coli-specific serine hydroxymethyltransferase (glyA) gene, along with C. hepaticusspecific glycerol kinase gene primers, has also been developed as a diagnostic tool to simultaneously detect and differentiate these three pathogens in poultry and environmental samples (Van et al, 2018).…”
Section: Introductionmentioning
confidence: 99%